A T-cell engaging bispecific antibody with a tumor-selective bivalent folate receptor alpha binding arm for the treatment of ovarian cancer - Brian C. Avanzino; Kirthana Prabhakar; Pranjali Dalvi; Sharon Hartstein; Hannes Kehm; Aarti Balasubramani; Andrew A. Boudreau; Ben Buelow; Karen Chang; Laura M. Davison; Suhasini Iyer; Vidyut Kalwit; et al. (OncoImmunology)
The use of T-cell engagers (TCEs) to treat solid tumors is challenging, and several have been limited by narrow therapeutic windows due to substantial on-target, off-tumor toxicities due to the expression of low levels of target antigens on healthy tissues. Here, we describe TNB-928B, a fully human TCE that has a bivalent binding arm for folate receptor alpha (FRα) to selectively target FRα overexpressing tumor cells while avoiding the lysis of cells with low levels of FRα expression. The bivalent design of the FRα binding arm confers tumor selectivity due to low-affinity but high-avidity binding to high FRα antigen density cells. TNB-928B induces preferential effector T-cell activation, proliferation, and selective cytotoxic activity on high FRα expressing cells while sparing low FRα expressing cells. In addition, TNB-928B induces minimal cytokine release compared to a positive control TCE containing OKT3. Moreover, TNB-928B exhibits substantial ex vivo tumor cell lysis using endogenous T-cells and robust tumor clearance in vivo, promoting T-cell infiltration and antitumor activity in mouse models of ovarian cancer. TNB-928B exhibits pharmacokinetics similar to conventional antibodies, which are projected to enable favorable administration in humans. TNB-928B is a novel TCE with enhanced safety and specificity for the treatment of ovarian cancer.